You are on page 1of 5

LECTURE 3

Nonhomogeneous Linear Systems


We now turn our attention to nonhomogeneous linear systems of the form
dx
(1)
= A (t) x (t) + g (t)
dt
where A (t) is a (potentially t-dependent) matrix and g (t) is some prescribed vector function of t. As in
the last lecture, we shall concentrate on 2 2 linear systems; as they are simple to compute and yet they
still retain the essential features of the general case.
Just as in the case a single nonhomogenous linear ODE, the general solution of (1) will be of the form
x (t) = xp (t) + xo (t)
where xp (t) is a particular solution of (1) and xo (t) is the general solution of the corresponding homogeneous
equation
dx
= A (t) x (t) .
(2)
dt
(This afterall is a consequence of the linearity of the system, not the number of equations.) And so, just as
in the case of a single ODE, we will need to know the general solution of homogeneous system (2) in order
to solve the nonhomogeneous system (1).
1. Diagonalizable Systems with Constant Coefficients
Lets begin with the simple 2 2 system of the form
dx
= Ax (t) + g (t)
(3)
dt
where A is a constant (i.e. t-independent) diagonalizable matrix. Let (r1 , ), and (r2 , ) be the eigenvalue/eigenvector pairs for A. We then have
x(1) (t) = er1 t

x(2) (t) = er2 t

as two fundamental solutions of (2). Recall that if we form a matrix C by using the eigenvectors and
as, respectively, the first and second columns then


r1 0
C1 AC =
D
0 r2
And so if we define
(4)

y = C1 x

h (t) = Ct g (t)

and multiply both sides of (3) from the left by C1 we get


 dy
d
dx
=
C1 x =
C1
dt
dt
dt
C1 (Ax (t) + g (t)) = C1 Ax (t) + C1 g (t) = C1 ACC1 x (t) + C1 g (t)
= Dy (t) + h (t)
1

2. GENERAL DIAGONALIZABLE SYSTEMS

Thus, we get
(5)
or

or

dy1
dt
dy2
dt

dy
= Dy (t) + h (t)
dt
 

 

r1 0
y1 (t)
h1 (t)
=
+
0 0
y1 (t)
h2 (t)

dy1
r1 y1 = h1 (t)
dt
dy2
(6b)
r2 y2 = h2 (t)
dt
Thus, the change of variable (4) allows us to convert the original system into an uncoupled pair of inhomogeneous ODEs.
(6a)

Recall that the general solution of


(7)

y + p (t) y = g (t)

1
y=
(t)

Z

C
(t) g (t) +
(t)

where

(t) = exp


p (t) dt

In the cases at hand



p (r)

g (t)

r1
r2

,
,

a constant
a constant

, a constant

h1 (t)
h2 (t)

and accordingly the solutions of (6a) and (6b) are


Z
r1 t
y1 (t) = e
er1 t h1 (t) dt + c1 er1 t
Z
y2 (t) = er2 t er2 t h2 (t) dt + c2 er2 t
Hence, we can write
R

er1 t R er1 t h1 (t) dt + c1 er1 t
y (t) =
er2 t er2 t h2 (t) dt + c2 er2 t
as the general solution of the auxiliary, decoupled system (5).


To recover the general solution of the original system, all we have to do is multiply the solution y (t) from
the left by C, as

(8)
x (t) = CC1 x (t) = C C1 x (t) = Cy (t)
2. General Diagonalizable Systems

Recall that the general solution of a single linear ODE


y 0 + p (x) y = g (x)

(9)
is given by
(10)

y=

1
(x)

Z
(x) g (x) dx +

C
(x)

Z
,

(x) = exp

Let me state this result a little differently. First, note that if g (x) = 0, then
C
y=
(x)
and so
1
(x)


p (x) dx

2. GENERAL DIAGONALIZABLE SYSTEMS

is interpretable as a fundamental solution for the corresponding homogeneous problem


y 0 + p (x) y = 0.
Let me denote by (x) this fundamental solution:
(x) (x)

 Z

= exp p (x) dx

Then in terms of the fundamental solution (x) of the corresponding homogeneous problem, the general
solution of nonhomogeous equation (9) is
Z
1
(100 )
y = (x) (x) g (x) dx + C (x)

In fact, the general solution of a nonhomgeneous system


dx
= A (t) x (t) + g (t)
dt

(11)

can also be expressed in terms of the fundamental solutions of the corresponding homogeneous problem
dx
= A (t) x (t)
dt

(12)

Suppose that the homogeneous system (12) has been solved in such a way that we can express its general
solution in terms of a fundamental matrix (t)1
x0 (t) = (t) c

dx0
= A (t) x0 (t)
dt

I claim that
Z
x (t) (t)

(13)

1 (t) g (t) dt + (t) c

is then the general solution of


dx
= A (t) x (t) + g (t)
dt
Before demonstrating this claim, however, note that (13) is a very straightforward generalization of the
solution(100 ) of a single nonhomogeneous linear ODE to a system of nonhomogeneous linear ODEs.
1In other words, suppose we have found n independent solutions (1) (t) , . . . , (n) (t) of an n n homogeous linear system
dxo
dt

= A (t) xo and have rewritten the right hand side of expression of the general solution as a linear combination of the
fundamental solutions
x0 (t) = c1 (1) (t) + + cn (n) (t)
as a matrix product

x0 (t) = (1) (t)


|

c1
.

(n) (t)
..
|
cn
|

(t) c

2. GENERAL DIAGONALIZABLE SYSTEMS

As for the demonstration that (13) is a solution of 11, thats easy




Z
d
d
1
x (t) =
(t) (t) g (t) dt + (t) c
dt
dt
 

Z
 Z

d
d
d
1
1
(t) g (t) dt +
=
(t) g (t) dt + (t)
(t) c
dt
dt
dt
Z

= (A (t) (t)) 1 (t) g (t) dt + (t) 1 (t) g (t) + A (t) (t) c


Z
= A (t) (t) 1 (t) g (t) dt + (t) c + g (t)
= A (t) x (t) + g (t)
The step



Z

d
1 (t) g (t) dt
(t) 1 (t) g (t)
dt
is just the application of the fundamental theorem of calculus.
(t)

Example 3.1.
dx1
= 2x1 x2 + et
dt
dx2
= 3x1 2x2 + et
dt
This set of differential equations corresponds to an inhomogeneous system x = Ax + g (t) with


 t 
2 1
e
A=
,
g (t) =
3 2
et
We shall first find the fundamental matrix for the corresponding homogeneous system x = Ax. This means
finding the eigenvalues r1 , r2 of A, the correponding eigenvectors 1 , 2 and then forming the matrix

|
|
(t) = er1 t 1 er2 2
|
|
each column of which being a fundamental solution.
Now

0 = det (A I) = det

2
3

1
2

= 2 4 + 3 = ( 1) ( + 1)


=1
=

=
v=1

N ullSp (A I) = N ullSp
 
1
=
1


= 1

v=1

N ullSp (A I) = N ullSp
 
1
=
3

1
3

1
3

1
1

3
3

and so when we can take



r1 = 1 ,
r2 = 1

1 =
,

2 =

1
1



1
3



=


= N ullSp




= N ullSp

1
0

3
0

= 1, 1
1
0

1
0





2. GENERAL DIAGONALIZABLE SYSTEMS

the fundamental matrix for the homogenous x = Ax is


 t

e
et
(t) =
et 3et
Using the formula


1



1
d b
=
c a
ad bc
we find
 t


1 3et
1
3e
et
1
=
(t) = t
et
et
e (3et ) et et
2 et
We can now plug into the formula
Z
x (t) = (t) 1 (t) g (t) dt + (t) c
a
c

b
d

et
et

for the general solution of x = Ax + g (t). We have


 t

  t

e
et
c1
e c1 + et c2
(t) c =
=
et 3et
c2
et c1 + 3et c2
and

 t 
et
e
dt
et
et

1 2t
3
2 2e
=
dt
12 e2t + 21
 R 3 1 2t 

2 e  dt
R 2 1 2t
2 e + 12 dt
 3

1 2t
2t + 4e
=
14 e2t + 12 t

1 (t) g (t) =

1
2
Z 

3et
et

And so
Z
(t)

1 (t) g (t) dt =
=

et
et

1 t
4e
1 t
4e

et
3et

1 2t
3
2t + 4e
1 2t
4 e + 12 t

2t
2t



6t + e
1 + 2te 
6t + e2t 3 + 6te2t

Thus, finally we have


Z
x (t) = (t) 1 (t) g (t) dt + (t) c
   t
 1 t

e c1 + et c2
e 6t + e2t 1 + 2te2t 
4
+
= 1 t
2t
et c1 + 3et c2
3 + 6te2t
4 e 6t + e
: :

You might also like